Pengaruh Teknologi Gadget Pada Perkembangan Pendidikan Sosial Siswa Kelas 3 Sekolah Dasar - Sayyidah Nafisah; Afakhrul Masub Bakhtiar (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
Abstract In this digital age, technology can easily spread throughout the world with very fast and rapid development. As with gadgets where gadgets are used by almost all groups from parents to children. As is the case with elementary school age children, not many elementary school age children do not have their own gadgets. Therefore the researchers conducted this research to find out whether there were negative and positive impacts on the educational development of grade 3 elementary school children. This research was conducted using a qualitative method with a descriptive approach, in which the results of this study were taken from interviews with parents and class teachers as well as observations. Indeed, basically gadgets have a positive impact, namely to help the learning process and are able to increase children's knowledge to recognize new foreign vocabulary. In addition, gadgets themselves also have a negative impact on children, namely children will feel addicted to playing gadgets which contain online games and social media which are currently being loved by children at elementary school age. As parents, you should always supervise your children so they don't play gadgets too often, let alone forget the time and forget their school assignments. Keyword: The influence of gadget, Educational Development, Elementary School.